Improving the impact of didactic resident training with online spaced education. Issue 6 (26th April 2013) - Gyorki, David E.; Shaw, Tim; Nicholson, James; Baker, Caroline; Pitcher, Meron; Skandarajah, Anita; Segelov, Eva; Mann, G. Bruce
Abstract Background Educational programmes are frequently developed to improve the knowledge of medical trainees. The impact of a programme may be limited if there is no follow‐up to reinforce the message. Online Spaced Education (SE) has been developed to address this limitation. This study was performed to assess whether an SE programme would improve the impact of a didactic seminar. Method A randomized trial of an online SE programme occurred as part of the 2010 Clinical Oncology Society of Australia Breast Cancer Trainee Workshop. Consenting participants were randomized to undertake SE or not and were then invited to undertake a 22‐question knowledge test. A questionnaire was administered relating to the perceived value of the SE programme. Participants consisted largely of surgical and medical oncology trainees. Results Two hundred people attended the workshop and 97 consented to randomization. Thirty‐eight of 49 randomized to the SE group commenced the SE course. Seventy‐one percent of participants answered each question at least once and 55% of participants completed the entire programme. Fifty‐nine participants completed the post‐test. The SE participants performed significantly better than the control group (P < 0.05). The questionnaire was completed by 26 of the SE group. Ninety‐two percent strongly agreed or agreed that SE would improve their practice and 96% agreed that SE effectively reinforced key aspects of workshop. Conclusion This study demonstrates the utility of SE to increase knowledge retention following a face‐to‐face workshop. The programme was very well received by the participants and may be an appropriate reinforcing methodology for other similar seminars.